Environmentally Conscious Behavior Through Ecoliteracy Activities At Sekolah Alam Depok - Syaifudin, Syaifudin (International Journal of Business, Law, and Education, 2023)
The background of this research addresses the issue of the public's lack of attention to the surrounding environment, which was observed by the researcher prior to conducting the study. This is evidenced by the presence of some students who still litter and the general lack of student awareness towards the environment. The aim of this research is to identify strategies to enhance environmentally conscious behavior through ecoliteracy activities at Sekolah Alam Depok. The research method used is descriptive qualitative. The data obtained includes the results of interviews, observations, and documentation. The data analysis technique used is SWOT analysis. The results of this research indicate strategies that can enhance environmentally conscious behavior through various ecoliteracy activities.